The role of the neuroinflammation and stressors in premenstrual syndrome/premenstrual dysphoric disorder: a review - Cheng, Ming; Jiang, Zhaoshu; Yang, Jie; Sun, Xu; Song, Nan; Du, Chunyu; Luo, Zhenliang; Zhang, Zhen (Frontiers in Endocrinology, 2025)
Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) are prevalent emotional disorders in females, characterized by cyclic variations in physiological stress responses and emotional symptoms that correspond with the menstrual cycle. Despite extensive research, the underlying causes of these disorders remain elusive. This review delves into the neurobiological mechanisms connecting stress-induced neuroinflammation with PMS/PMDD. Additionally, it traces the conceptual development and historical context of PMS/PMDD. The review further evaluates clinical evidence on the association between PMS/PMDD and stress, along with findings from both clinical and animal studies that link these disorders to inflammatory processes. Additionally, the neurobiological pathways by which inflammatory responses may play a role in the pathogenesis of PMS/PMDD were elucidated, including their interactions with the hypothalamic-pituitary-ovary (HPO) axis, serotonin—kynurenine (5-HT—KYN) system, GABAergic system, brain-derived neurotrophic factor (BDNF), hypothalamic-pituitary-adrena(HPA)axis and. Future research is encouraged to further investigate the pathogenesis of PMS/PMDD through the perspective of neuroinflammatory responses.